Domestic exposure to endotoxin and respiratory morbidity in former smokers with COPD. (14th December 2015) - Bose, S.; Rivera‐Mariani, F.; Chen, R.; Williams, D.; Belli, A.; Aloe, C.; McCormack, M. C.; Breysse, P. N.; Hansel, N. N.
Abstract: Indoor air pollution has been linked to adverse chronic obstructive pulmonary disease (COPD) health, but specific causative agents have not yet been identified. We evaluated the role of indoor endotoxin exposure upon respiratory health in former smokers with COPD. Eighty‐four adults with moderate to severe COPD were followed longitudinally and indoor air and dust samples collected at baseline, 3 and 6 months. Respiratory outcomes were repeatedly assessed at each time point. The associations between endotoxin exposure in air and settled dust and health outcomes were explored using generalizing estimating equations in multivariate models accounting for confounders. Dust endotoxin concentrations in the main living area were highest in spring and lowest in fall, while airborne endotoxins remained steady across seasons. Airborne and dust endotoxin concentrations were weakly correlated with one another ( r s = +0.24, P = 0.005). Endotoxin concentrations were not significantly associated with respiratory symptoms, rescue medication use, quality of life, or severe exacerbations. In vitro whole‐blood assays of the pro‐inflammatory capacity of PM10 filters with and without endotoxin depletion demonstrated that the endotoxin component of indoor air pollution was not the primary trigger for interleukin‐1 β release. Our findings support that endotoxin is not the major driver in the adverse effects of indoor PM upon COPD morbidity.